1984
DOI: 10.2307/1541226
|View full text |Cite
|
Sign up to set email alerts
|

ALANINE UPTAKE BY ISOLATED ZOOXANTHELLAE OF THE MANGROVE JELLYFISH,CASSIOPEA XAMACHANA.I. TRANSPORT MECHANISMS AND UTILIZATION

Abstract: Freshly isolated zooxanthellae of the mangrove jellyfish Cassiopea xamachana were found to take up exogenous l4 C-alanine and incorporate the radiolabel into various cellular components. Transport was highly Na + -dependent and lacked stereospecificity. Competition experiments with several L-amino acids and alanine analogs exhibited varying degrees of competitive inhibition, and these results are discussed in relation to the well described neutral amino acid transport systems known for many eukaryotic cells. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Besides amino acids, ammonium and nitrate have been shown to be sources of nitrogen in cultured and symbiotic Symbiodinium [6] , [50] . The investigation using the synchrotron radiation spectroscopy has further confirmed that symbiotic Symbiodinium (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Besides amino acids, ammonium and nitrate have been shown to be sources of nitrogen in cultured and symbiotic Symbiodinium [6] , [50] . The investigation using the synchrotron radiation spectroscopy has further confirmed that symbiotic Symbiodinium (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…symbionts, compared to cultured strains, as well as growth capability on a wide range of organic natural and synthetic nitrogen compounds as sole nitrogen source (Le Den Dooren, 1967;McAuley, 1986McAuley, , 1987. Uptake of amino acids such as methionine, cysteine, alanine and taurine by Symbiodinium has also been demonstrated for in vitro (Carroll and Blanquet, 1984;Deane and O'Brien, 1981) and possibly for in hospite cells (Cook, 1971;Steen, 1986). Similar to the Hydra-Chlorella system, uptake of taurine, cysteine and methionine is more efficient in symbiotic vs. cultured Symbiodinium cells, with some indication for an inducible uptake system that increases the substrate affinity at low taurine concentrations (Deane and O'Brien, 1981;Wang and Douglas, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We also know virtually nothing about "reverse translocation" of carbon compounds, the transfer of metabolites from host to symbiont, though it is known that isolated symbionts can take up a range of organic and inorganic molecules from the surrounding medium (39,40,82,89,151,344). The uptake of 35 S by symbiotic dinoflagellates from food ingested by Aiptasia sp.…”
Section: Translocation Of Photosynthetic Productsmentioning
confidence: 99%